Moderating effect of self-efficacy on cognitive, emotional and social intelligence towards job performance in banking industry - Amrollahifar, Jamak; Ali, Mass Hareeza; Dato Mansor, Zuraina; Jaharuddin, Nor Siah; Yajie, Guo (Advances in Social Science Research Journal, 2023)
Although the services sector is one of the sectors that anchored the country’s economy growth in 2019 in Malaysia, this sector lacks in growth and need to be pushed for greater productivity. Particularly, financial sector has the most contribution to the service sector. Meanwhile, the banking sector of Malaysia has gone through profound and rapid changes in the last few years. This study aims to examine the moderating effect of self-efficacy on the relationship between cognitive, emotional and social intelligence towards job performance in the Malaysian local commercial banks using survey data obtained from 436 employees. The Partial Least Square method is employed to study the link. The findings indicate that self-efficacy moderates the relationship between cognitive and emotional intelligence towards job performance. Nevertheless, contrary to the claims of scholars, the study finds no evidence of any moderation effect of self-efficacy on the relationship between social intelligence towards job performance. Limitation and suggestion for the future research are also discussed.